Diagnostic accuracy of the FRAIL scale plus functional measures for frailty screening: a cross- sectional study. Issue 3 (2022) - Rodríguez-Laso, Ángel; Martín-Lesende, Iñaki; Sinclair, Alan; ourdet, Sandrine; Tosato, Matteo; Rodríguez-Mañas, Leocadio
No abstract available